Karakteristik Pengeringan Lapisan Tipis Irisan Singkong (Manihot Esculenta) Pada Beberapa Ketebalan Menggunakan Experimental Dryer - Ramly Lumanu; Lady C. Ch. E. Lengkey; Daniel P. M. Ludong (COCOS, 2019)
Abstract Drying a thin layer of cassava slices to the thickness of the slices is done using the Experimental Dryer. Drying is carried out at a temperature of 60 ̊C, observations are carried out every 15 minutes for the first 2 hours then every 1 hour until reaching equilibrium water content. The purpose of this study was to determine the drying characteristics of cassava slices and to determine the equation model between water content to time, drying rate to time, drying rate to water content, and analyze temperature changes in each sample in the dryer during the drying process. This research was conducted at the Post Harvest Laboratory of Agricultural Engineering, Faculty of Agriculture, Sam Ratulangi University, Manado. The research method uses experimental methods, observations and calculations are plotted in a graph and analyzed descriptively. Drying is done until the equilibrium water content. The tools used in the drying process are thermocouples, ovens, desiccators, analytical scale, digital scale. The material used cassava slices with 2 thicknesses are 3 and 6 mm. The results showed that during the drying process there were differences in temperature at 2 thicknesses. Mathematical model of the relationship of water content to time at a thickness of 3 mm is found in sample 2 with a moisture content reaching 1.6% WB after drying process for 7-8 hours with an exponential equation y = 28,602e-0,44x and R² = 0,8256 while at a thickness of 6 mm in sample 1 it reached 2% WB after drying for 11 - 12 hours with the exponential equation y = 41,161e-0.327x and R² = 0.8957. The drying rate model with at 3 mm thickness is with y = 52.336e-0.729x and R2 = 0.9613 and at 6 mm thickness the drying rate model with time is y = 31.845e-0.677x and R2 = 0.9826 while the model drying rate of water content at a thickness of 6 mm with y = 0.3119e0.0992x and R² = 0.7597. Keywords: Cassava Bulbs, Characteristics, Drying and thin film models.